Perbandingan Efek Salin dan Kristaloid Seimbang pada Pasien dengan Penyakit Ginjal Kronis dalam Setting Perioperatif : Narative Review - Suandika, Made; Thoriq Maulana Amru, Akmal; Muhammad Ilyas, Syarif (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Intravenous fluid management is a critical component of perioperative care in patients with chronic kidney disease (CKD). The type of fluid administered may influence acid–base balance, electrolyte status, and the risk of acute kidney injury (AKI). This article aims to review the latest scientific evidence comparing the effects of 0.9% saline and balanced crystalloids in CKD patients in the perioperative setting. A narrative review was conducted by searching PubMed, Scopus, ScienceDirect, and Google Scholar using keywords related to saline, balanced crystalloids, CKD, perioperative care, and AKI. Eligible articles included randomized controlled trials, meta-analyses, and systematic reviews published between 2015–2024. Results: Evidence from multiple studies indicates that balanced crystalloids are superior in maintaining acid–base stability, reducing chloride levels, and lowering the incidence of AKI compared to saline. Large trials such as SMART, SALT-ED, and BEST-Fluids demonstrated reduced major adverse kidney events and delayed graft function in the balanced group, although mortality outcomes remain inconsistent. Balanced crystalloids provide greater physiological advantages and renal protection compared to saline in CKD patients undergoing surgery. While mortality reduction has not been consistently observed, current evidence supports the use of balanced crystalloids as the preferred perioperative fluid, particularly in patients at high risk of AKI.